The Role of Hadith in Enhancing Quranic Literacy - Saleh, Fauzi (El-Sunan: Journal of Hadith and Religious Studies, 2025)
This study explores the integral role of hadith in enhancing Quranic literacy by demonstrating how prophetic traditions function as interpretive, applicative, and complementary elements to the Quranic text. Utilizing a qualitative-descriptive approach based on library research, the study examines primary Islamic sources—including classical tafsir and authenticated hadith collections—and contemporary scholarly literature. The findings show that hadith fulfills three critical functions: (1) clarifying Quranic verses through interpretive explanation (bayān al-tafsīr), (2) reinforcing Quranic commands via consistent prophetic practice (bayān al-taqrīr), and (3) providing legal elaboration on matters not explicitly addressed in the Quran (bayān al-tashrīʿ). Furthermore, hadith contextualizes revelation through the transmission of asbāb al-nuzūl and serves as the ethical embodiment of Quranic values in real life. The study concludes that integrating hadith into Quranic studies is not optional but imperative, as Quranic literacy without prophetic guidance risks remaining abstract, fragmented, and misapplied. This research affirms the necessity of hadith as a methodological, pedagogical, and spiritual anchor for meaningful engagement with the Quran.